2010
DOI: 10.1371/journal.pone.0011733
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Inhibits Autophagy in Bystander Macrophage/Monocytic Cells through Src-Akt and STAT3

Abstract: Autophagy is a homeostatic mechanism of lysosomal degradation. Defective autophagy has been linked to various disorders such as impaired control of pathogens and neurodegeneration. Autophagy is regulated by a complex array of signaling pathways that act upstream of autophagy proteins. Little is known about the role of altered regulatory signaling in disorders associated with defective autophagy. In particular, it is not known if pathogens inhibit autophagy by modulation of upstream regulatory pathways. Cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
96
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 80 publications
(124 reference statements)
6
96
1
Order By: Relevance
“…In agreement with these findings it has also been demonstrated in dendritic cells (DCs) that rapamycin-mediated autophagy induction exerts a better anti-BCG vaccine response [31]. This raises the possibility of therapeutic manipulation of cell signalling to restore autophagy in HIV-1 infection [30].…”
Section: Mtor and Impaired Function Of Innate Immunity During Hiv Infsupporting
confidence: 65%
See 1 more Smart Citation
“…In agreement with these findings it has also been demonstrated in dendritic cells (DCs) that rapamycin-mediated autophagy induction exerts a better anti-BCG vaccine response [31]. This raises the possibility of therapeutic manipulation of cell signalling to restore autophagy in HIV-1 infection [30].…”
Section: Mtor and Impaired Function Of Innate Immunity During Hiv Infsupporting
confidence: 65%
“…Thus, stopping phagocytosis of opportunistic pathogens such as Mycobacterium avium complex, Pneumocystis carinii, Toxoplasma gondii or Candida albicans by peripheral blood monocytes, tissue macrophages and monocyte-derived macrophages following in vivo and in vitro HIV-1 infection has been documented [29]. Late-stage development of opportunistic infections has therefore been attributed to defective monocyte/macrophage signalling and function in HIV-infected individuals [30]. mTOR activation inhibits the destruction of pathogenic microorganisms by macrophages by inhibiting autophagy; rapamycin restores this macrophage inhibition.…”
Section: Mtor and Impaired Function Of Innate Immunity During Hiv Infmentioning
confidence: 99%
“…In particular, IFN-g, TNF-a, IL-1a, and IL-1b increase autophagosome formation in macrophages (3,4,15), whereas IL-4, IL-13, and IL-10 inhibit autophagy (5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 98%
“…HCV induces autophagy through the Rab5 and class III PI3K Vps34 pathway (55). Human immunodeficiency virus inhibits autophagy through the Src-Akt and STAT3 pathway (59). We have found that PCV2 induces autophagy in PK-15 cells (68).…”
mentioning
confidence: 85%